2006
DOI: 10.1037/0022-006x.74.4.687
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains during therapy of social phobia.

Abstract: The present study investigated the phenomenon of sudden gains in 107 participants with social phobia (social anxiety disorder) who received either cognitive-behavioral group therapy or exposure group therapy without explicit cognitive interventions, which primarily used public speaking situations as exposure tasks. Twenty-two out of 967 session-to-session intervals met criteria for sudden gains, which most frequently occurred in Session 5. Individuals with sudden gains showed similar improvements in the 2 trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
109
7
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 52 publications
(134 reference statements)
17
109
7
1
Order By: Relevance
“…This finding is consistent with those of other studies, which recorded an early change in the fifth treatment session (e.g., [54][55][56]). …”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with those of other studies, which recorded an early change in the fifth treatment session (e.g., [54][55][56]). …”
Section: Discussionsupporting
confidence: 83%
“…For example, by examining frequent assessments during treatment for depression, Tang and DeRubeis (1999) found that change occurs in sudden gains rather than in a linear pattern. In contrast, Hofmann, Schulz, Meuret, Moscovitch, and Suvak (2006) found few sudden gains in the treatment of social anxiety disorder. Answering questions about the pattern and timing of change will also be of interest to the scientist-practitioner concerned with maximizing outcome and understanding the psychotherapeutic process.…”
mentioning
confidence: 94%
“…The percentage of sudden gains was 19% for social phobia (Hofmann, Schulz, Meuret, Moscovitch, & Suvak, 2006), 17% for a sample with various anxiety disorders (Norton, Klenck, & Barrera, 2010), 43% for panic disorder (Clerkin, Teachman, & Smith-Janik, 2008) 4 and 16% for clients with generalized anxiety disorder when all the clients seen at intake were included (Present et al, 2008). However, in this last study, with the sample restricted to those with a Beck Anxiety Inventory (BAI) score of 15 or greater at session one (which excluded more than half the original sample), the percent with sudden gains rose to 35%.…”
Section: Case MIXmentioning
confidence: 99%